Analysis Of Politeness Strategies Used By The Main Character In Home Alone 1 - Ramadya Abitza; Alfian Alfian; yenti yenti (English Language, Linguistics, Literature, And Education Journal, 2021)
The objective of this research is to discuss the politeness strategies in Home Alone 1 movie. Home Alone 1 tells the story of a child name Kevin who tries to keep his house from burglars. Kevin uses politeness strategies to fulfill his ambitions. The purposes of this study are as follows: (1) to know kinds of politeness strategy used by the main character in the home alone 1 movie, (2) to know how the main character used the politeness strategies. This article uses a pragmatic approach from Eva Alcon Soler and Aricia Martinez Flor (2008), and politeness from Brown and Levinson theory (1978). The methods are qualitative research and descriptive method to analyze the data. The researcher used the documentation to collect the data while source of the data was taken from the dialogues and the scene in Home Alone 1 movie. The finding in this thesis shows that Kevin uses politeness strategies to keep his house from burglars and communicate with other characters. (1) Four types of politeness strategies used by Kevin are bald on record, positive politeness, negative politeness, and off record, (2) Kevin uses the politeness strategy in form of direct communicating and indirect communicating.